FREKUENSI IBU HAMIL TM II DAN III DALAM MELAKUKAN SENAM HAMILÂ DI BPM NY. MEILA FAMILIA RUSDIANA, Amd.Keb DESA WATES UMPAK KECAMATAN TROWULAN KABUPATEN MOJOKERTO - Eka P, Veryudha; Nurhadiyanti, Fithri (JURNAL KEPERAWATAN SEHAT, 2015)
The gymnastics pregnancy beneficial to maintain and optimize physical balance, maintaining a healthy pregnancy. Pregnant women who follow pregnancy exercise can lead delivery smoothly, by utilizing the power and capabilities as well as possibleso that delivery run normally and smoothly. With pregnancy exercise also increases the strength of uterine muscle contractions in order to achieve optimal results towards the birth canal. The purpose of this study was to determine the frequency of maternal TM II and III in doing pregnancy exercise on BPM Ny. Meila Familia Rusdiana, Wates village Amd.keb pedestals District Trowulan 2014 research design was descriptive. The population in this study were all pregnant mothers TM II and III in BPM Ny. Meila Familia Rusdiana, Amd. Keb Wates Village District Trowulan pedestals as many as 17 people. The sampling technique used was non-probability sampling sampling saturated type. This research was conducted in BPM Ny. Meila Familia Rusdiana, Amd. keb Wates Village District Trowulan pedestals on 19 to 23 July2014, data was collected using a questionnaire sheet. Data processing by means of editing, coding, scoring, tabulating. The results showed that the average respondent perform second-trimester pregnancy exercise was 2 and in the third trimester was 2 Pregnant women are still reluctant to do pregnancy exercise, this is because the psychological condition of the mothers abdomen, causing the mother growing difficulty to move and lazy to physical exercise. The frequency of pregnancy exercise during pregnancy trimester II and III are stil lrelatively few. It is expected that health workers can provide counseling or health education or by putting up posters on how to do a proper pregnancy exercise classes and provide pregnant women and provide facilities to mothers in health care, especially in prenatal care.Keywords:Pregnancy, Pregnant Gymnastics